Teaching Medical Translation - Wakabayashi, Judy (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1996)
AbstractThe main difficulties specific to medical translation are students' lack of medical knowledge and their unfamiliarity with medical terminology and phraseology. These difficulties can be partially overcome by a bilingual introduction to the key anatomical terms, diagnostic terms, symptomatic terms, operative terms, laboratory tests, and clinical procedures related to each of the body systems. Together with ample practice in actual translation, a medical translation course should also include information on useful resource materials; Latin and Greek roots, affixes and combining forms; common medical abbreviations; "lay" terms vs medical terms; medical English style; and the standard format of medical journal articles.